Application of forward models to crystal orientation refinement. Issue 6 (3rd November 2017) - Singh, Saransh; Ram, Farangis; De Graef, Marc
Abstract : Two algorithms reliant on physics‐based forward models are proposed to refine crystal orientations: a multi‐resolution brute‐force local search and a derivative‐free optimization. The efficacy of these methods is evaluated for the electron backscatter diffraction and electron channeling pattern modalities using simulated patterns with known orientations. Abstract : Two approaches are proposed for the refinement of electron diffraction pattern indexing. The approaches require two basic ingredients: an accurate physics‐based forward model and an algorithm to search the local orientation neighborhood. Forward models for electron backscatter diffraction (EBSD) and electron channeling pattern (ECP) modalities are coupled with either a multi‐resolution brute‐force search algorithm or a bound optimization by quadratic approximation algorithm. The efficacy of the methods is evaluated for varying levels of error in the pattern projection center. The EBSD modality shows an orientation improvement when the projection center error is within ±1% of the full detector width, whereas the ECP modality shows improvement up to a ±5% error. The algorithms are applied to an experimental EBSD scan for partially recrystallized 90/10 brass; the results show that the refinement is necessary to remove the artifacts introduced by the discrete sampling nature of the dictionary indexing method. Finally, a pattern center correction factor is derived for orientations obtained from dictionary indexing for large‐area EBSD scans.